PENGARUH PEMBERIAN BERBAGAI KONSENTRASI HORMON IBA (INDOLE BUTYRIC ACID) TERHADAP PERTUMBUHAN AKAR PADA STEK BATANG TANAMAN BUAH NAGA (HYLOCEREUS UNDATUS) - SHOFIANA, ARINI (Universitas Negeri Surabaya, 2013)
Dragon fruit (Hylocereus undatus) is a plant of high economic value. With increasing consumer demand for dragon fruit, it is necessary to the provision of quality seeds. Effective seed multiplication is done by stem cuttings. One effort to increase the percentage growth of cuttings is to use hormone IBA (Indole Butyric Acid) to stimulate root growth, because the IBA has a more stable chemical content and workability for longer so that it can stimulate root growth. The purpose of this study was to determine the effect of various concentrations of IBA on root growth in cuttings of dragon fruit plants and determine the optimal concentration of IBA for root growth in cuttings of dragon fruit plants. The study was conducted experimentally using a randomized block design with one treatment factor, namely the concentration of IBA include 0 ppm, 500 ppm, 1000 ppm, 2000 ppm and 4000 ppm. Factor is repeated 5 times to obtain 25 samples treatment. Parameters, that were measured, were the percentage of root cuttings, root length, and root biomass. Data was analyzed using analysis of variance (ANOVA) one-way and followed by Duncan test to determine differences among treatments. The results showed that various concentrations of IBA hormone affected positively on root growth of dragon fruit plant cuttings, and the optimal concentration of IBA on root growth was 2000 ppm.